PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 009 BUKIT KAPUR - Harahap, Masniari Harahap; Witri, Gustimal Witri; Marhadi, Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research is motivated by the lack of science learning outcomes of students of class III B Chalk Hill Elementary School 009.  This research aims to improve science learning outcomes of students of class III B Chalk Hill Elementary School 009 with “ the application of Cooperative Learning Numbered Heads Together Type (NHT)”.  The design of this study is action research (CAR) conducted as many as two cycles, each cycle consisting of two meetings and one-time daily tests. From this study the activity of teachers' observations obtained at the first meeting of the first cycle is 62.5% category enough, a second meeting was 70.8% both categories, the first meeting of the second cycle category 87.5% very good, 91.7% second meeting category very well. While the student activity observed in the first cycle the first meeting 58.3% category enough, 66.7% second meeting both categories, the first meeting of the second cycle 75% good category, the second meeting 87.5% very good category. Judging from the results of the activities of teachers and students from the first cycle to the second cycle has increased. For the study results can be seen in the increase of the daily test cycle I and cycle II. In the first cycle test results at each cycle also increased, the first daily test cycle average of 71.8 or 17.5% increase, the second daily test cycle average of 79.8 or 30.6% increase. From this research it can be concluded that the application of Cooperative Learning Model Numbered Heads togethr Type (NHT) to Improve Student Learning Outcomes IPA III Class B Chalk Hill Elementary School 009. Keywords: Numbered Head Together (NHT), Science Learning Outcomes